The Depolymerization of Kappa Carrageenan Using Peracetic Acid - Nofri Sandria; Uju Uju; Pipih Suptijah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Kappa carrageenan is a galactose polysaccharide which is easily hydrolyzed on acidic and stable onalkaline solution. Kappa carrageenan is widely used in food industries, pharmaceuticals and cosmetics asthickening, stabilizing, and gelling agents. Peracetic acid (PAA) with the empirical formula CH3COOOHis strong oxidizing agent as a selective agent of delignification. The aims of this study were to determinethe effect of peracetic acid concentration on the characteristics of depolymerization kappa carrageenansuch as, yield, total solubility, viscosity, molecular weight, microstructure, and its functional groups. Theresult of this research showed that kappa carrageenan depolymerization had yield 32.78-98.11%, totalsolubility 23.83-96.68%, viscosity 1.01-26.59 cP, and molecular weight 5.89-199.31 kDa. The higher of PAAconcentration used, the less yield, the increased solubility, lower viscosity, and smaller molecular weights.Depolymerization treatment using 2% PAA caused changes to the microstructure and the function groupkappa carrageenan depolymerization.